2017
DOI: 10.1038/srep46720
|View full text |Cite
|
Sign up to set email alerts
|

Dual mechanisms of grain refinement in a FeCoCrNi high-entropy alloy processed by high-pressure torsion

Abstract: An equiatomic FeCoCrNi high-entropy alloy with a face-centered cubic structure was fabricated by a powder metallurgy route, and then processed by high-pressure torsion. Detailed microscopy investigations revealed that grain refinement from coarse grains to nanocrystalline grains occurred mainly via concurrent nanoband (NB) subdivision and deformation twinning. NB–NB, twin–NB and twin–twin interactions contributed to the deformation process. The twin–twin interactions resulted in severe lattice distortion and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 62 publications
4
30
0
Order By: Relevance
“…The generally low texture strength may be also caused by twinning. In addition to twinning, in CrFeCoNi MEA Wu et al [31] observed nanobands and attributed the significant grain refinement to concurrent nanoband subdivision and deformation twinning. Instead of mechanical twinning, during HPT at LNT a strain-induced phase transformation takes place.…”
Section: Microstructure Developmentmentioning
confidence: 99%
“…The generally low texture strength may be also caused by twinning. In addition to twinning, in CrFeCoNi MEA Wu et al [31] observed nanobands and attributed the significant grain refinement to concurrent nanoband subdivision and deformation twinning. Instead of mechanical twinning, during HPT at LNT a strain-induced phase transformation takes place.…”
Section: Microstructure Developmentmentioning
confidence: 99%
“…The β phase in regions rich in Mo and W was heavily stabilized, so the high strain induced by cold rolling was accommodated by extensive dislocation activity, such as dislocation multiplication, accumulation, interaction, tangling, and spatial rearrangement. The dislocation cell structure subdivided a grain into many fine grains at the nanometre scale 13 , 31 , 32 , 43 45 . In contrast, in the β phase regions containing fewer β stabilising elements, the deformation strain was accommodated by martensite transformation 13 , 32 , 43 , 44 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The deformation mechanisms commonly found in conventional metallic materials, such as dislocation slip and deformation twinning, also play important roles in HEAs and MEAs. However, attributed to the low stacking-fault energy (SFE), short-range ordering effect and local elemental fluctuations, dislocation slip and deformation twinning can be very chaotic in HEAs and MEAs during plastic deformation [ 6 , 20 , 21 , 22 , 23 , 24 , 25 ]. It is well known that the propensity for deformation twinning is inversely proportional to the SFE.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the propensity for deformation twinning is inversely proportional to the SFE. The SFE of the Cantor HEA is at the lower bond ~20–25 mJ/m 2 [ 25 ]. Thus, the presence of high densities of deformation twinning is found to be a major mechanism of the plastic strain in the Cantor HEA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation